Big Data and Democracy - Efthymiou–Egleton, Theoharris-William; Sidiropoulos, Symeon; Spanos, Evangelos; Stougiannou, Elli (HAPSc Policy Briefs Series, 2020)
One of the biggest questions in the digital age pertains to the relevance of democracy in the era of big data. Unquestioningly, the digital revolution is growing at a rapid pace and many are being caught unaware by its impact in various avenues. The amount of data available has been doubling year on year, and the conditions of usage have been evolving at a pace faster than the policies are being provided to ensure proper usage. Many have started looking for ways of turning big data into big money, an aspect that is coming at the expense of the democratic values countries have upheld for generations. Instead, it is becoming a huge problem as the history of humankind is becoming more documented now and messages are easier to send compared to a century ago. Understanding the impact of big data on democracy can help accentuate the best way of improving democratic institutions and their ability to overcome the pressure coming from evolving technology.